The Impact of Emotional Feedback and Elaborated Feedback of a Pedagogical Agent on Multimedia Learning - Lang, Yueru; Xie, Ke; Gong, Shaoying; Wang, Yanqing; Cao, Yang (Frontiers in Psychology, 2022)
This study aimed to explore the impact of emotional feedback and elaborated feedback provided by a pedagogical agent (PA) on learners’ emotions, intrinsic motivation, agent perception, cognitive load, and transfer performance in multimedia learning. The experiment was conducted based on an actual undergraduate course. Undergraduate students (N = 117) were randomly assigned to one of four conditions, where PA’s feedback differed by emotional feedback (with vs. without) and elaborated feedback (elaborated feedback vs. knowledge of results). Results revealed that emotional feedback reduced learners’ confusion, activated intrinsic motivation, and enhanced agent perception. In addition, elaborated feedback improved intrinsic motivation, agent perception, transfer performance but reduced germane cognitive load. Surprisingly, there was no significant interaction between emotional feedback and elaborated feedback. These findings had implications for designing a PA with feedback fulfilling learners’ emotional and cognitive needs to maximize multimedia learning.